Tuberkulóza v Ceské republice v roce 2007 - Homolka, J; Krejbich, F; Holub, J (Casopis lekaru ceskych, 2009)
BACKGROUND: The number of notified tuberculosis cases in the Czech Republic decreased in the year 2007. 871 new tuberculosis cases and relapses were reported in the year 2007 (8.4/100 000 inhabitants). METHODS AND RESULTS: 744 cases were pulmonary tuberculosis (7.2/100 000) and from them 506 were definite pulmonary cases (4.9/100 000). In 2007 266 smear-positive cases of pulmonary tuberculosis were diagnosed. The decreasing trend in tuberculosis incidence reported since 1998 has continued. Only 14.7% of new cases of pulmonary tuberculosis were discovered by active case-finding. CONCLUSIONS: Next targets of tuberculosis control in the Czech Republic must be an active case-finding in high-risk groups and monitoring of latent tuberculosis infection.
Keywords: Tuberculosis, Pulmonary; Humans; plicní tuberkulóza; Česká republika; lidé; Tuberculosis; tuberkulóza; incidence; Incidence; Czech Republic